Pengaruh Model Pembelajaran Problem Based Learning dengan Mind Mapping terhadap Motivasi dan Hasil Belajar Siswa di SMA Negeri 1 Sekongkang - Astuti, Astuti; Masiah, Masiah; Nurhidayati, Siti (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research is motivated by the still dominant use of conventional learning models that are centered on teachers, which has an impact on low motivation and student learning outcomes. This study aims to determine the effect of the Problem Based Learning (PBL) model with the Mind Mapping strategy on student motivation and learning outcomes at SMA Negeri 1 Sekongkang. The research method used is a quasi-experiment with a purposive sampling technique, involving 52 students as samples. The research instruments are in the form of motivation questionnaires and learning outcome tests. The results of the analysis show that the PBL model with Mind Mapping has a significant effect on student motivation and learning outcomes, with a significance value of 0.000 (p <0.05) and an F value = 10.004. These findings indicate that the application of active and visual learning models can increase the effectiveness of learning.